Pengaruh Model Pembelajaran POE (Predict-Observe-Explain) Terhadap Hasil Belajar IPA Materi Perubahan Sifat Benda Kelas V SDN 17 Binamu Kabupaten Jeneponto - Sitti Hasmiyanti Sapiuddin; Hilmi Hambali; A.Muafiah Nur (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2023)
The Influence of the POE (Predict-Observe-Explain) Learning Model on Science Learning Outcomes on Changes in the Properties of Objects for Class V Sdn 17 Binamu, Jeneponto Regency. Thesis. Department of Elementary School Teacher Education. Faculty of Teacher Training and Education. Muhammadiyah University of Makassar. Supervisor I Hilmi Hambali and Supervisor II A. Muafiah Nur.This research aims to determine the effect of the POE (Predict-Observe-Explain) learning model on learning outcomes in science material on changes in the properties of objects in class V. This research is a quantitative research using quasi-experimental research design with experimental methods in the form of pretest posttest group control design, with two groups, namely the control group and the experimental group.The data in this research were analyzed using descriptive statistical analysis techniques and inferential statistics. The results show that there is an influence of the POE (Predict-Observe-Explain) model in science subjects on science learning outcomes in material on changes in the properties of objects for class V SDN 17 Binamu, Jeneponto Regency. This can be seen in the average posttest score for the control class which only reached 66.74, while the average posttest score for the experimental class reached 82.83. Based on hypothesis testing using the independent sample t test, the tcount value = 6.279, while the ttable value = 2.015. Based on the results obtained because tcount > ttable (tcount = 6.279 > ttable = 2.015), thus Ho is rejected and H1 is accepted.